Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 1250 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Micropterus salmoides (Lacepède, 1802)", "Geometry POLYGON((-110.04 22.62,-110.04 30.45,-96.26 30.45,-96.26 22.62,-110.04 22.62))", "HasGeospatialIssue is false" ] } The dataset includes 1250 records from 26 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0053903-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences